PERANCANGAN SISTEM INFORMASI KELENGKAPAN RESUME MEDIS GUNA KLAIM BPJS MENGGUNAKAN METODE WATERFALL - Dewi Meita Sari; Lusiana Dwiputri Ramdhani; Meira Hidayati (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
Medical Resume is a record/summary of results of entire period of patient care and treatment carried out by health personnel concerned. Medical Resume used as a requirement for one of BPJS claims at hospital. The use of information technology at this time must continue to grow, to create quality information. Method used is quantitative descriptive analysis, data collection used observation techniques, and software development method used Waterfall method through stages of needs analysis, system design, code writing and implementation. Purpose of this study was to determine the Design of a Medical Resume Completeness Information System for BPJS Claims at Sartika Asih Hospital Bandung. Medical Resume Completeness System at Sartika Asih Hospital is still done manually with Microsoft Excel so it is less effective, it is necessary to have an efficient information system to make it easier to check the completeness of the medical resume if there is a medical resume that staff can return it immediately to doctor who is responsible for replenishment. By the information system created, it is hoped that it will make it easier for staff to check the completeness of medical resumes quickly and efficiently so that the BPJS claim process is not obstructed.